Analisis Rantai Pasok Alpukat di Kecamatan Bandungan, Kabupaten Semarang - muhammad aidi Helyanda (Universitas Widya Gama Mahakam, 2020)
The research aims to analyze supply chain conditions and measure avocado marketing efficiency in Bandungan District, Semarang Regency. The research began in March ₋ June 2020. Methods of research used survey methods. The method of sampling farmers using the purposive sampling method, as much as 40 people. The sampling of marketing agencies was conducted by snowball sampling techniques. A total of 14 people consisted of Pegepul, wholesalers, and retailers. Primary data collection is done by interviews with respondents based on a prepared questionnaire. Data analysis methods used qualitative and quantitative descriptive methods and computation of marketing efficiency. The results showed that the condition of the avocado supply chain in Bandungan district was quite good. The target supply chain is clear, good supply chain structure, resources are adequate, although the implementation of management has not been said to be good, one of them because there is no contractual agreement between marketing institutions so that the amount of avocado sold can not be predicted. The supply chain business process indicates that the product flow in the avocado supply chain moves from the farmer to the consumer, the flow of information goes two-way, i.e. from farmer to consumer or vice versa and the financial flow is moving from consumer to farmer. In the business process, there is a slight obstacle because on the flow of avocado products and information is not yet well integrated, there is no definite cycle so that the delivery time or volume of production can not be predicted well. Marketing activities in the supply chain of the Bandungan district are quite efficient judging from the value of farmer's share (≥ 40%) And the value of the marketing margin of channels 1 Rp 11,800,-, Channel 2 Rp 11,374,-and channel 3 Rp 14,674,-.